Writing a Quality Thesis/Dissertation for MS or PhD Degree A Note for Researchers, MS and PhD Students - Islam, MT; Baten, MA (Journal of Environmental Science and Natural Resources, 2012)
Thesis or dissertation is a research report concerns a problem or series of problems in the area of applied or basic research. Abstract should contain all elements of the thesis in an extreme shorter form. Need to try to accommodate the description of the works including introduction, design and methodology within 2-3 sentences. Key findings of the experiments should be written in very brief. After findings, key words are written. The key words have to be different from the words in the title and to be arranged alphabetically. Introduction covers (i) identification of scientific problem stated in brief, (ii) critical analysis of relevant background information of the study to justify the problem using past research reports, (iii) identification of scientific information gap based on background analysis, (iv) formulation of the hypothesis, i.e making researchers best guess at the answer to the problem, and (v) formulation of specific objective(s) of the work. Review of literature has two reasons. One is to explain the results, need to collect only the relevant information and the other is to find out the gap or unexplored area for the study, that the designed work is either original or some works done still gaps are remained and/or different workers on the line to find contrast results. In materials and methods, the materials including treatments used in the study are recorded. Listed parameters are also mentioned. New technique(s) should be described in detail, other wise mention name only if necessary giving a brief note. Mention the layout/design of the experiments and analysis procedure. In results and discussion, we describe results chronologically and conclude logically. Presentation of the same result both in table and graph is prohibited. Summary and conclusion include introduction (importance) about the works, methodology, design/layout, etc. in very brief. In conclusion key message should be provided. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11596 J. Environ. Sci. & Natural Resources, 5(1): 301-308, 2012